PENDEKATAN SAINTIFIK DALAM MENINGKATKAN MOTIVASI BELAJAR PENDIDIKAN AGAMA ISLAM - Munib, Abdul (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2017)
The scientific approach is an innovative learning process designed specifically for students to actively construct the concept of knowledge through several processes or stages by observing to perform an identification of a problem, and from the results of the observation students are expected to be able to formulate the problem dilajutkan by formulating hypotheses, collect data with various techniques, and analyze data, and draw conclusions and communicate concepts, laws or principles that are "discovered". The application of a scientific approach in learning will involve the skills of the process of observing, classifying, measuring, predicting, explaining, and then concluding. With this saintific approach, it is expected that students will be happy to participate in learning activities and can improve their learning motivation to follow the learning process and will ultimately have an impact on their learning achievement. Motivational factors can be said to be key to understanding the process of self-adjustment, motivation as well as emotional infrastructure needs which are internal forces that cause tension and imbalance in organisms. In general, motivation will not arise, but motivation will rise if there is a great interest, the learning process will work well if all students have a great interest in following the learning process.